PENERAPAN MODEL PEMBELAJARAN PROBLEM POSING UNTUK MENINGKATKAN PRESTASI BELAJAR PESERTA DIDIK PADA POKOK BAHASAN HIDROKARBON DI KELAS XI MIPA SMAN 12 PEKANBARU - Silvi Octaviani Asmi; Usman Rery; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purposes of research were to know improved of student achievement and the effect of the application problem posing learning model to increased student achievement on the subject of hydrocarbon in Class XI MIPA SMAN 12 Pekanbaru. This research was a form of experimental research with the design randomized control group pretest-posttest. The study population was students of class XI MIPA at SMAN 12 Pekanbaru. The samples were students of class XI MIPA 3 as experimental class and class XI MIPA 2 as the control class. The experimental class was applied Problem Posing learning model, while the control class using conventional learning model. Data were analyzed by using t-test to created a prediction and N-gain test to choiced the improvement category of students achievement. Results from the study showed tcount>ttable 5,32>1.67) and category increase student achievement in the experimental class at 0,80 with high katergori while the experimental class category increase student achievement by 0.69 with category soit can be concluded the implementation of Problem Posing learning model can improve the student achievementon the subject of Hydrocarbonin class XI MIPA SMAN 12 Pekanbaru.Key Words: Learning Achievement, Learning Model Problem Posing, Hydrocarbons